Галузевому Державному архіву Служби безпеки України – 10 років (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
State archive of Security service of Ukraine (now Branch state archive of Security service of Ukraine) was established according to the decree of government of Ukraine of the 1st of April, 1994. The article dedicated to the main directions of work and achievements of archive for the time of its existence.